1992
DOI: 10.1080/03079459208418861
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomical differences in varus and valgus deformities of chick limbs suggest different aetio‐pathogenesis

Abstract: SUMMARYLeg deformities were investigated in three flocks of broilers (n = 600, n = 817, n = 361). Two types of twisted legs were characterized: varus of the tarsal joint (1 to 3% of birds) and valgus of the tarsal joint (30 to 40% of birds) with mild, intermediate and severe valgus angulation. Varus angulation appeared suddenly, between 5 and 15 days of age, was unilateral in 80% of cases and affected mainly the right limb. Medial tendinous displacement was always present and led to severe locomotor handicap a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 12 publications
6
46
0
1
Order By: Relevance
“…For example, after beak trimming, hens and turkeys gave fewer pecks (Gentle and Hunder, 1991). To avoid musculoskeletal pain, birds can limp or take relieving postures, ranging from a slight change in the positioning of the leg to a complete loss of support by the painful member (Kestin et al, 1992;Leterrier and Nys, 1992). Lame chickens spent more time lying and walked less (Weeks et al, 1997 and2000), and turkeys with musculoskeletal disorders were less generally active than controls (Duncan et al, 1991).…”
Section: Postural and Behavioural Indicatorsmentioning
confidence: 99%
“…For example, after beak trimming, hens and turkeys gave fewer pecks (Gentle and Hunder, 1991). To avoid musculoskeletal pain, birds can limp or take relieving postures, ranging from a slight change in the positioning of the leg to a complete loss of support by the painful member (Kestin et al, 1992;Leterrier and Nys, 1992). Lame chickens spent more time lying and walked less (Weeks et al, 1997 and2000), and turkeys with musculoskeletal disorders were less generally active than controls (Duncan et al, 1991).…”
Section: Postural and Behavioural Indicatorsmentioning
confidence: 99%
“…Time spent standing, eating and scratching did not differ between S1 and S2 birds when they were fed the same diet, only time spent exploring tended to be lower in S2 birds when fed the E1P2 diet. The clinical observations indicated that gait score was mainly impaired due to rotated tibias and varus-valgus angulations of the tarsal joint (Leterrier and Nys, 1992). Mean gait score improved in the sequential feeding groups (Table 4).…”
Section: Sequential Feeding and Leg Problems 1661mentioning
confidence: 94%
“…The latter is most often associated with a medial tendinous displacement. 'Unilateral' or 'bilateral' varus were further distinguished as suggested by Riddell (1983) and Leterrier and Nys (1992), but these data were pooled for the analysis. All animals were thus classified as healthy, valgus or varus.…”
Section: Animalsmentioning
confidence: 99%
“…McCullagh and Nelder (1989) (Leterrier and Nys, 1992;Riddell, 1992) (1985), and Albert and Chib (1993) (Johnson and Kotz, 1970). Assuming that y* is the largest amongst all the y * values, the probability of observing the ith category corresponds to:…”
Section: Statistical Modelmentioning
confidence: 99%
See 1 more Smart Citation